The Protestant interest : New England after Puritanism - Kidd, Thomas S. (Yale University Press, 2004)
During the early 18th century, New England witnessed the end of Puritanism and the emergence of a revivalist movement that culminated in the evangelical awakenings of the 1740s. This text shows how New Englanders abandoned their hostility towards Britain, instead viewing it as the chosen leader in the fight against Catholicism.